Determination of the Cs distribution along a line of sight by the Zeeman splitting in an inhomogeneous magnetic field. (23rd August 2018) - Wimmer, C; Lindauer, M; Fantz, U
Abstract: Large-scale sources for negative hydrogen ions are required for the neutral beam injection of the ITER fusion device. Caesium is used for the conversion of hydrogen atoms into negative ions. The combination of moderate background vacuum conditions (10 −7 –10 −6 mbar), the high reactivity of Cs, continuous evaporation of Cs and plasma-enabled redistribution of Cs and Cs + forms a complex dynamics. ELISE (extraction from a large ion source experiment) is a half ITER-source scale experiment. A tunable diode laser absorption spectroscopy (TDLAS) diagnostic at the resonant Cs 6 2 S1/2 –6 2 P3/2 transition (852 nm) has been applied to the source in order to measure the density of neutral Cs close to the conversion surface and thus gaining a better insight into the Cs dynamics. An inhomogeneous magnetic field created by permanent magnets (≈25–320 G) is located along the line-of-sight (LOS) of the TDLAS, leading to a varying effect of the Zeeman splitting of the concerning Cs states and thus the absorption line profile along the LOS. In long plasma pulses at ELISE, a change of the Cs absorption line profile takes place, which can be attributed to a variation of the Cs density profile along the LOS. In order to attribute a measured line profile to a certain magnetic field strength and thus a certain position along the LOS, absorption spectra with a defined B-field at a Cs vapor cell using the same diagnostic system have been measured. The strong broadening of the measured line profile at ELISE after several 10 s of plasma indicates that neutral Cs is mainly located in the area of high magnetic field strength, i.e. close to the side wall. A correlation between the measured Cs density and the source performance exists during the beginning of the pulse and is lost in this later phase.